1962
DOI: 10.1172/jci104613
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hypergammaglobulinemia on Albumin Metabolism in Hyperimmunized Rabbits Studied With Albumin-I131*

Abstract: Depressions of the serum albumin level are seen in clinical and in experimentally produced hyperglobulinemia (1-3); dextran infusions are also associated with hypoalbuminemia (4). However, the mechanisms for the production of these changes in albumin levels are not clearly defined. A colloid osmotic regulatory system has been postulated which effects control through either changes in plasma volume (1) or alterations in albumin metabolism (4). Previous studies employing dextran infusions supported the existence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

1964
1964
1990
1990

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 18 publications
6
18
0
Order By: Relevance
“…These results agree with what has been noted at low albumin levels, namely, that albumin synthesis does not respond to changes in albumin concentrations per se (12,18,19). It had been proposed that albumin syn-thesis may be controlled by a regulatory system responding to changes in colloid osmotic pressure; however, the infusions were isosmotic with the plasma, and a change in colloid osmotic pressure probably did not occur (12,19). Apparently, therefore, when albumin concentrations or pool size are increased, as in the present study, or diminished as in proteinuria (18), changes in albumin degradation are predominant.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results agree with what has been noted at low albumin levels, namely, that albumin synthesis does not respond to changes in albumin concentrations per se (12,18,19). It had been proposed that albumin syn-thesis may be controlled by a regulatory system responding to changes in colloid osmotic pressure; however, the infusions were isosmotic with the plasma, and a change in colloid osmotic pressure probably did not occur (12,19). Apparently, therefore, when albumin concentrations or pool size are increased, as in the present study, or diminished as in proteinuria (18), changes in albumin degradation are predominant.…”
Section: Discussionsupporting
confidence: 92%
“…Apparently, therefore, when albumin concentrations or pool size are increased, as in the present study, or diminished as in proteinuria (18), changes in albumin degradation are predominant. In contrast, the administration of dextran or the production of persistently elevated gamma globulin levels results in a reduction in the rate of albumin synthesis rather than a change in the rate of degradation (12,19). In the presence of an exogenous source of serum protein, albumin levels are maintained primarily by an increase in albumin degradation, indicating that albumin degradation and synthesis change independently of each other.…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to the observations in human myeloma and in hyperimmunized animals where in the presence of hypergammaglobulinemia the gamma globulin half-life is usually shortened (18,19). The lack of effect of AD on albumin half-life is also in accord with studies on hypergammaglobulinemic rabbits (20), and is probably related to different degradatory mechanisms for these two serum proteins.…”
Section: Serum Proteinsupporting
confidence: 89%
“…In a series of papers based on experimental reduction and expansion of the albumin pool size Rothschild and his colleagues (36)(37)(38)(39) concluded that the quantity of albumin degraded was related to albumin concentration or pool size. It would be of interest to know whether a fall in albumin catabolic rate is brought about by reduction of the serum albumin concentration or by contraction of either the intra-or extravascular pool.…”
Section: 26) Cohen and Hansenmentioning
confidence: 99%
“…These findings may correspond to our plasmapheresis experiments with ad libitum feeding and suggest that albumin synthesis will increase when protein is lost from the body, provided dietary nitrogen is adequate. In their series of experiments Rothschild and his colleagues (36)(37)(38)(39) concluded that synthesis of albumin was regulated by the colloidal osmotic pressure of plasma, not by the albumin concentration. This problem may not finally be answered until a direct method of measuring albumin synthesis is applied.…”
Section: 26) Cohen and Hansenmentioning
confidence: 99%